Adaptation and Validation of the Indonesian Version of the Short Moral Disengagement in Bullying Scale - Ila Nurlaila Hidayat; Wan Nurul Izza Wan Husin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2026)
Moral disengagement (MD) is a cognitive mechanism that plays a significant role in the development of negative behaviors, including bullying. In this context, a valid and reliable measure of MD is needed to understand the dynamics of bullying in schools. The development, modification, or adaptation of MD scale intended to measure bullying-related MD among school students in Indonesia remains limited. Therefore, this study aimed to adapt and validate the Short Moral Disengagement in Bullying Scale (MDBS) for use in the Indonesian context. The cross-cultural adaptation of the instrument used the forward-backward translation method and was administered to 301 students. The results showed that all six items reported adequate factor loadings (.41–.71), reporting satisfactory item representation of the underlying construct. The measurement model exhibited a good fit to the data (χ²/df = 1.317; CFI = .988; RMSEA = .032). In addition, the scale showed acceptable reliability (CR = .769; AVE = .363) and remained robust across different groups, supporting the measurement stability. The AVE provided new insights regarding the contextual boundaries of collectivistic culture for the universal cognitive structure of MD. The Indonesian version of the Short MDBS could be used with students in junior high school or equivalent grades 7 through 9.